Acceleration of electron bunches using periodic dielectric structures with and without coating - Vasyliev, A.V.; Bolshov, O.O.; Galaydych, K.V.; Povrozin, A.I.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2021)
The numerical studies of high acceleration gradients obtaining for the dielectric laser accelerators (DLA) based on-chip structures with one-sided laser excitation at a wavelength of 800 nm are presented. The electron flight heights of 200 and 400 nm over a structure are presented. The influence of the geometric parameters of the structures on the acceleration gradients was also investigated. A study of changes in the acceleration gradients of structures, when applying a gold coating on these types of structures, has been carried out.